Long‐term remission of small cell lung cancer after reactivation of tuberculosis following immune‐checkpoint blockade: A case report. Issue 5 (17th January 2021) - Sirgiovanni, Mattia; Hinterleitner, Clemens; Horger, Marius; Atique, Naushad Bijoy; Lauer, Ulrich M.; Zender, Lars; Hinterleitner, Martina
Abstract: Immune‐checkpoint inhibitors (ICIs) provide a promising treatment option for advanced tumors including small cell lung cancer (SCLC). Nevertheless, in addition to immune‐related adverse events (irAEs), an increased risk of infection including tuberculosis has been previously described. Here, we report a case of long‐term remission of a patient with SCLC after reactivation of lung tuberculosis following ICI therapy. Our case illustrates the complexity of ICI‐associated immune modulation in tuberculosis. Since new lesions in lung cancer patients are commonly associated with tumor progression, infections with mycobacterial tuberculosis may be underdiagnosed in lung cancer. Abstract : Our case illustrates the complexity of ICI‐associated immune modulation in tuberculosis. Since new lesions in lung cancer patients are commonly associated with tumor progression, infections with mycobacterial tuberculosis may be underdiagnosed in lung cancer.